Effect of the application of nitrogen-fixing microorganisms on the growth of maize (Zea mays L.) crop - Rivero Herrada, Marisol (2024)
The application of nitrogen-fixing microorganisms in agricultural crops has shown multiple benefits, especially in plant nutrition. In the present investigation, the agronomic response of the corn crop (Zea mays L.) was evaluated, to the application of nitrogen-fixing microorganisms. The experiment was used a randomized complete block design (DBCA) in a factorial arrangement 3x3 +1 control, with three repetitions. The applied treatments: T1. Paenibacillus polymyxa 2,0 L ha-1; T2. P. polymyxa 3,0 L ha-1; T3. P. polymyxa 4,0 L ha-1; T4. Azotobacter 2,0 L ha-1; T5. Azotobacter 3,0 L ha-1; T6. Azotobacter 4,0 L ha-1; T7. P. polymyxa + Azotobacter 2 L ha-1; T8. P. polymyxa + Azotobacter 3,0 L ha-1; T9. P. polymyxa + Azotobacter 4 L ha-1 and T10. Witness (no application). The variables evaluated were plant height, stem diameter, days to flowering and crop yield. The results showed that 55 days after sowing (DDS) of the crop, a good growth of the corn plants with a height of 182.01 cm and a stem diameter of 20.14 mm was obtained with the application of the treatment. T9. Paenibacillus polymyxa + Azotobacter in doses of 4.0 L ha-1. In addition, the insertion of the cob was also at 120 cm height of the plant, for this same treatment.